Case Report of Malignant Lymphoma of the Breast - ASHARIATI, AMI; DJATMIKO, ARIO; ALI, ISKANDAR (Indonesian Journal of Cancer, 2014)
Four cases of breast malignant lymphoma (BML) are discussed, diagnosed and managed. The issue of diagnosing BML, showed how different these 4 cases were, in particular in the imaging ultrasonography (USG). Generally, the USG of ductal carcinoma is irregular solid mass, while the USG of BML is compliant with cystic forms. Case 1 is 68 years old woman with left breast tumor. USG revealed hypoechoic lesion in the left breast with FNA result of malignant lymphoma, but still differential diagnosis with ductal carcinoma of the breast Mamma. Case 2 is a 52 years old woman who had left breast tumor. The USG revealed malignant lesion, left axilla node positive, although FNA result was ductal carcinoma, after simple mastectomy, the frozen section revealed malignant lymphoma. Case 3 is a 51 years old woman, USG of the left breast revealed malignant lesion, left axilla node positive, and excision biopsy revealed non-Hodgkinâs lymphoma diffuse large cell. Case 4 is a 51 years old woman, the USG revealed irregular hypoechoic lesions in both breasts and left supraclavicula node 5 mm. Core biopsy revealed bilateral breast non Hodgkinâs lymphoma subcutaneous, T-cell lymphoma. The therapeutic management of breast lymphoma is controversial and is not fully established yet. A strategy consisting of three cycles of CHOP followed by involved-field radiation therapy is reportedly superior to eight cycles of CHOP alone.